The law of shipbuilding contracts - Curtis, Simon; Gaunt, Ian; Cecil, William (Lloyd's shipping law library, 2020)
"The Law of Shipbuilding Contracts examines the principles of English contract law as these apply to shipbuilding. The leading text on shipbuilding and marine construction, widely used by the global maritime community, this new edition is updated to account for the "long tail" effects of the global economic crisis on the sector. The authors provide expert analysis on the key shipbuilding contract forms, including sections dealing with agreements ancillary to the shipbuilding contract and ship conversion contracts, together with - for the first time - contracts for the construction of offshore oil and gas vessels and units. The new edition has been comprehensively updated, including commentary on recent High Court decisions on shipbuilding contracts and, in particular, associated refund guarantees. The contractual and legal consequences of global economic turbulence and the resultant increase in the number and size of disputes in the shipbuilding sector are discussed, alongside coverage of other contemporary regulatory and legal issues resulting from environmental pressures and the trend for "cleaner", more efficient tonnage. A comprehensive and authoritative resource, this book is essential reading for buyers and charterers of newbuilding tonnage, shipbuilders and offshore construction yards, shipbrokers, banks and other finance providers, lawyers and insurers working in the maritime and offshore oil and gas sectors, as well as students of maritime law"--